Legal Liability of Business Actors for Damaged Smartphone Products from a Consumer Protection Perspective - Kefianto, Kefianto; Tarina, Dwi Desi Yayi (Journal of Law, Politic and Humanities, 2025)
This research discusses business actors whose products are damaged in large quantities. The purpose of this study is to examine how the responsibility of business actors for the products sold and analyze whether the responsibilities of business actors are in accordance with statutory regulations, especially Law Number 8 of 1999 concerning Consumer Protection. The research method used is normative legal research, with a case approach and legislative approach. Research data is obtained from primary legal sources in the form of laws and regulations, doctrine, scientific literature, and the results of relevant academic studies. The results showed that business actors have carried out their obligations by providing after-sales service in the form of unit repairs. However, in this case, it was found that many consumers experienced the same damage, so the business actor should take another step, namely recall the product from distribution.